A netnographic examination of tourists' memorable hotel experiences. Issue 1 (2nd January 2018) - Sthapit, Erose
Abstract: The present study utilized netnography to explore tourists' memorable hotel experiences. Customer-generated content on TripAdvisor was analysed for identifying the components that contribute to tourists' memorable hotel experiences in Helsinki and Rovaniemi, in Finland. Ten keywords "memorable", "unforgettable", "extraordinary", "notable", "enduring", "decisive", "out of the world", "will never forget", "once in a lifetime", and "rememberable" were used to gather the online narratives. The data used in this study include 272 online narratives pertaining to tourists' experiences of 47 different hotels. The study assumed a passive, covert lurker position to avoid interfering with the naturally ongoing discussion. A grounded theory approach was used to analyse the data. The findings reveal three components that contribute to tourists' memorable hotel experiences: a comfortable bed, the friendly attitude of hotel staff, and a delicious breakfast with plenty of choice as well as a good restaurant service at the hotel. Tourists' memorable hotel experiences can be linked to the novelty and refreshment dimensions of memorable tourism experience (MTE) scale. The study found evidence of negative MTEs and supports studies suggesting the need to be critical of the MTE scale dimensions.